Analisis pengaruh V/C ratio lalu lintas kendaraan terhadap tingkat polusi udara berdasarkan volume lalu lintas kendaraan (studi di kawasan persimpangan Mall SKA Kota Pekanbaru) - Muhammad Yevizal; Aras Mulyadi; Ferry Fatnanta (Pelantar Press, 2018)
Completion of the transportation problems in the city of Pekanbaru currently only looked at in terms of congestion, but not touching insights from environmental aspects such as performance air pollution and noise levels. This research was conducted at the observation point road ahead Repair Tambusai lord Eastern Daihatshu, road Tuanku Tambusai West Side Mall SKA, North Soekarno Hatta street front retail outlets, street front Soekarno Hatta South Hotel Ibis Pekanbaru. V / C Ratio highest in the afternoon rush hour on the road ahead Tambusai lord Stations Daihatsu ie 0.86 pelyanan road performance E. Quality Standard ambient NOx emissions do not exceed the threshold of ambient quality standards, the NOx emission = 281.76 mg/m3. Quality Standard ambient CO emissions do not exceed the threshold of ambient quality standards, namely emission = 7456.79 mg/m3, the noise level over the limit of noise that is 71.41 dB (A). To balance the load reduction in pollutant emissions and noise levels at the flyover plan with the plan of special bus lane traffic volume assumptions have to move 25% of the transfer of the road users of private vehicles and motorbikes switch to using mass public transport vehicles ie Trans Metro bus Pekanbaru.